Quantitative Anatomic Comparison of the Extreme Lateral Transodontoid vs Extreme Medial Endoscopic Endonasal Approaches to the Jugular Foramen and Craniovertebral Junction. Issue 5 (29th November 2022) - Abramov, Irakliy; Labib, Mohamed A.; Houlihan, Lena Mary; Loymak, Thanapong; Srinivasan, Visish M.; Preul, Mark C.; Lawton, Michael T.
Abstract : BACKGROUND: Large, destructive intracranial and extracranial lesions at the jugular foramen (JF) and anterior craniovertebral junction (CVJ) are among the most challenging lesions to resect. OBJECTIVE: To compare the extreme lateral transodontoid approach (ELTOA) with the extreme medial endoscopic endonasal approach (EMEEA) to determine the most effective surgical approach to the JF and CVJ. METHODS: Seven formalin-fixed cadaveric heads were dissected. Using neuronavigation, we quantitatively measured and compared the exposure of the intracranial and extracranial neurovascular structures, the drilled area of the clivus and the C1 vertebra, and the area of exposure of the brainstem. RESULTS: The mean total drilled area of the clivus was greater with the EMEEA than with the ELTOA (1043.5 vs 909.4 mm 2, P = .02). The EMEEA provided a longer exposure of the extracranial cranial nerves (CNs) IX, X, and XI compared with the ELTOA (cranial nerve [CN] IX: 18.8 vs 12.0 mm, P = .01; CN X: 19.2 vs 10.4 mm, P = .003; and CN XI, 18.1 vs 11.9 mm, P = .04). The EMEEA, compared with the ELTOA, provided a significantly greater area of exposure of the contralateral ventromedial medulla (289.5 vs 80.9 mm 2, P < .001) and pons (237.5 vs 86.2 mm 2, P = .005) but less area of exposure of the ipsilateral dorsolateral medulla (51.5 vs 205.8 mm 2, P = .008). CONCLUSION: The EMEEA and ELTOA provide optimal exposures to different aspects of the CVJ and JF. A combination of these approaches can compensate for their disadvantages and achieve significant exposure.